Prospective Study of Medication Adherence Pattern in Chronic Obstructive Pulmonary Disease and Asthma Patient’s in Tertiary Care teaching Hospital - Fugate, Ajay R; Kadam, A M; Ganachari, M S (Indian Journal of Pharmacy Practice)
Lack of patient compliance with prescribed regimen is an important fascinating problem in medical care, especially in patients suffering from chronic illnesses. Asthma and Chronic Obstructive Pulmonary Disease (COPD) are the two main chronic lung disorders which are particularly vulnerable for medication non-adherence problem. Aim of the study was to assess medication adherence by self-report method to understand various determinants of medication non-adherence, and to enhance adherence using the strategies of counseling, education, and interviewing the patient. The prospective study was conducted for period of six months, assessed medication and inhaler adherence by administering Morisky self-reported questionnaires and inhaler technique were assessed by the standard checklist. Also reported the reasons for non-adherence.The study shows there was statistically significant increase in medication (P<0.001) and inhaler adherence score (P<0.001) and inhaler technique score (P<0.001) from baseline after pharmacist counseling regarding disease and medication. Comparison between various demographic factors like age, gender, diagnosis, duration of disease, and education status showed equal impact of pharmacist counseling on improvement of overall medication adherence score. Overall medication adherence and inhaler technique improvement was found to be statistically significant in asthma and COPD patients after counseling by pharmacist. The major reasons for medication non-compliance were felt better and stopped, high cost of medication, forgetfulness and lack of access to drug store/hospital.
Keywords: Asthma; COPD; Clinical pharmacist; Medication Adherence; Patient education